Role of Foam Sclerotherapy with Injection Ethanolamine Oleate for the Treatment of Venous Malformation in Head-Neck Region - Rahman, Mohammad Habibur; Naha, Abirvab; Majumder, Riashat Azim; Mahmud, Md Khalid; Jewel, Arif Mahmud; Tarafder, Kamrul Hassan; Chowdhury, A Allam; Rahman, Sheikh Hasanur (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Venous malformations (VMs) are a variety of low flow vascular malformations, which are developmental error of morphogenesis of veins where veins are dysplastic lined by quiescent or normal endothelium. Although surgical extirpation is the standard method for the treatment of vascular malformations, this procedure often leads to significant loss of motor function, nerve damage, or massive bleeding in patients which may endanger the life. Therefore, sclerotherapy has now been accepted as a less invasive alternative and good results have been obtained. Objectives: This study was conducted to evaluate the clinical outcomes after Foam sclerotherapy with injection Ethanolamine Oleate (EO) for the treatment of VMs in head-neck region. Methods: This quasi-experimental study was conducted in the Department of Otolaryngology- Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU). Forty-three patients with venous malformation in head neck region that had the inclusion criteria were enrolled as a study sample. The patients were diagnosed mostly clinically & confirmed by demonstrating non-pulsatile blood flow and venous space using Duplex ultrasound. The sclerosing solution 5% Ethanolamine Oleate (EO) was used in this study. Sclerofoam was produced using the Tessari method in 4:1 air to liquid ratio, the foam had been used within 60- 90 seconds. Results of the study were categorized as excellent, good, fair and poor. Ethical clearance was obtained from the Institutional Review Board (IRB) of BSMMU. Results: Among 43 patients 34(79.1%) patients underwent single session and 9(20.9%) were two sessions. All the lesions were responded to EO. Response to sclerotherapy categorized as excellent were in two third 29 (67.4%) patients and 14 (32.6%) had good response. No sessions resulted in poor responses. No complications occurred following any procedures. All of the sessions were performed as a day case basis without anesthesia. Conclusions: Foam sclerotherapy with injection EO appears to be safe and effective for the treatment of VMs in the head and neck region and should be considered when treating these complex lesions. Bangladesh J Otorhinolaryngol; October 2020; 26(2): 79-85